Pulmonary hemosiderosis with juvenile rheumatoid arthritis: a case report - Topaloğlu, Rezan; Kiper, Nural; Göçmen, Ayhan; Varan, Birgül; Saatçi, Ümit (The Turkish Journal of Pediatrics, 2000)
Pulmonary hemosiderosis may rarely be associated with juvenile rheumatoid arthritis or can develop during the course of the disease. We present a three-year-old boy with severe iron deficiency anemia (without any pulmonary symptoms) and arthralgia at the time of diagnosis. Two years after the initial diagnosis he developed pulmonary hemosiderosis and pauciarticular type of juvenile rheumatoid arthritis which progressed to seronegative polyarticular juvenile rheumatoid arthritis. He responded very well to prednisolone and was maintained well on low-dose alternate-day prednisolone and naproxen sodium treatment. This is the only case of association of these two diseases in our experience in both the Pediatric Rheumatology and Pediatric Respiratory Diseases Departments.